Story Face Strategy in Teaching Reading Narrative Text - Lumban Tobing, Devi Emelia; Harida, Eka Sustri; Siregar, Sri Rahmadhani (English Education : English Journal for Teaching and Learning, 2024)
The research study conducted at Grade X SMA Negeri 1 Simangumban demonstrated a significant positive effect of utilizing the Story Face Strategy on students' reading comprehension of narrative text. The experimental quantitative method with a pre-test and post-test design involving 44 randomly sampled students out of a population of 88 students revealed that students' comprehension of narrative text improved significantly after implementing the Story Face Strategy. TheT-test results (tcount  ttable), supported the accep-tance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0). Therefore, it can be inferred that the Story Face Strategy had a notable impact on enhancing students' reading compr- ehension of narrative text at Grade X SMA Negeri 1 Simangumban